Effect of cellulose acetate phthalate and polyethylene glycol on physical properties and release of theophylline from microcapsules - Amjad Hussain; Ahmad Mehmood Mumtaz; Muhammad Sohail Arshad; Nasir Abbas; Abida Latif; Rahat Shamim; Nadeem Irfan Bukhari; Khalid Hussain
ABSTRACT The present study describes the development of theophylline microcapsules by a non-solvent addition method and the effect of plasticizer addition on microencapsulation. The release was studied in distilled water and the data were analysed by various mathematical models for determining the mechanism of release. Prepared microcapsules were found to be spherical, free flowing and having more than 80% entrapped drug. The polymer - cellulose acetate phthalate and plasticizer - polyethylene glycol was considered to be affecting the properties of microcapsules including drug release (time for 50% drug release, T50). The formulation with the highest proportion of polymer and without plasticizer (F3) showed the slowest release with T50 = 4.3 h, while the formulation with lower proportion of polymer and 20% (w/w) plasticizer (F13 &14) showed the fastest release of drug with T50 values of 1.2 h and 1.3 h, respectively. The drug release from most of the formulations was found to be following Higuchi model. It is concluded from the results of the present study that cellulose acetate phthalate significantly affects the sustained release of the drug in water, whereas the addition of polyethylene glycol slightly enhances the drug release.